Developing formative authentic assessment instruments based on learning trajectory for elementary school - Anesa Surya; Aman Aman (REID (Research and Evaluation in Education), 2016)
This research aims to (1) develop research formative authentic assessment instruments based on learning trajectory that is eligible for the fourth grade students of elementary schools; and (2) develop formative authentic assessment instruments based on learning trajectory that is effective for the fourth grade students of elementary schools. This developmental study refers to the model developed by Borg Gall. The developmental design was grouped into four development procedures, consisting of: (a) Exploration, (b) development of the draft/prototype, (c) product testing and revisions, and (d) final validation. The experimental subjects are some pilot project elementary schools which used Curriculum 2013 in Ngawi Regency. The data were collected using interview guides, documentation, assessment sheets of the product instrument of authentic assessment, observation sheets of the students, achievement test, questionnaire responses of teachers and students. The data of the instrument reliability were analyzed in terms of item discrimination and item difficulty, and the agreement index was employed for the reliability of the instrument. The research finding reveals that the research instrument in terms of attitude assessment, assessment of knowledge and skills according to subject-matter experts and experts in evaluation is categorized as ‘very good’. The results of the item discrimination analysis show that nonnegative and item difficulties  range from easy to hard. The formative authentic assessment instruments are categorized as ‘reliable’ by the agreement index of ≥ 0.75.